Degradation of phenol in wastewaters via heterogeneous Fenton-like Ag/CeO2 catalyst. Issue 1 (February 2017) - Aneggi, Eleonora; Trovarelli, Alessandro; Goi, Daniele
Graphical abstract: Highlights: Silver-doped catalysts promote phenol degradation in mild conditions. Silver-doped ceria results to be the more efficient system. The activity is due to the participation of the silver/silver oxide in the reaction. The effect of silver can be explained on the basis of a radical mechanism. Abstract: In this study the oxidation of phenol via heterogeneous Fenton-like process over silver-based catalysts loaded on CeO2, ZrO2 and Al2 O3 has been evaluated. Structural and morphological properties were investigated by conventional techniques and catalytic tests were carried out in an autoclave at 343 K. Phenol conversion was evaluated by liquid chromatography-electrospray ionization mass spectrometry (LC-ESI-MS) measurements. The influence of pH and temperature on phenol conversion was also considered. Silver-doped ceria exhibited a good activity in the oxidation of phenol and the optimization of the reaction variables (pH and temperature) led to an increase of the activity reaching an almost complete degradation of the pollutant at pH = 2 and 343 K. The deactivation of the catalyst after up to five cycles were evaluated and the material resulted to be very stable. The present study highlights the potential of silver supported catalyst for the removal of organic compounds in wastewaters via heterogeneous Fenton-like system.